BRCA1 and Breast Cancer: Molecular Mechanisms and Therapeutic Strategies - Fu, Xiaoyu; Tan, Wei; Song, Qibin; Pei, Huadong; Li, Juanjuan (Frontiers in Cell and Developmental Biology, 2022)
Breast cancer susceptibility gene 1 (BRCA1) is a tumor suppressor gene, which is mainly involved in the repair of DNA damage, cell cycle regulation, maintenance of genome stability, and other important physiological processes. Mutations or defects in the BRCA1 gene significantly increase the risk of breast, ovarian, prostate, and other cancers in carriers. In this review, we summarized the molecular functions and regulation of BRCA1 and discussed recent insights into the detection and treatment of BRCA1 mutated breast cancer.